Kuda kepang Performance Form of the Wahyu Budoyo Studio in Legokkalong, Pekalongan Central Java Indonesia - Shadewi Noorita Prabandari; Sestri Indah Pebrianti (Universitas Pendidikan Indonesia, 2023)
Performing art has a cultural orientation from the supporting community in conveying values and moral messages which are conveyed implicitly in artistic elements in the form of themes, movements, accompanying music, costumes, make-up, floor patterns, song lyrics, props, lighting, and even the dancers' facial expressions. All elements of the dance form in the Kuda kepang dance also have several values that make researchers interested in researching the Kuda kepang dance at Sanggar Wahyu Budoyo. The aim of this research is to examine the form of the Kuda kepang dance at Sanggar Wahyu Budoyo. The research method used is a qualitative method with an etic and emic approach. By using an ethical and emic approach, the researcher obtained data in the form of the history of the formation of the Kuda kepang dance at Sanggar Wahyu Budoyo, interpreting the values contained in the Kuda kepang dance at Sanggar Wahyu Budoyo, and the verbal and non-verbal elements of the Kuda kepang dance at Sanggar Wahyu Budoyo. Data collection techniques use interviews, observation and documentation. The data validity technique uses source triangulation techniques. Data analysis techniques use data reduction, data presentation, and drawing conclusions.